2008
DOI: 10.1007/s00425-008-0741-1
|View full text |Cite
|
Sign up to set email alerts
|

Fast and reversible response of thylakoid-associated polyamines during and after UV-B stress: a comparative study of the wild type and a mutant lacking chlorophyll b of unicellular green alga Scenedesmus obliquus

Abstract: The functional and biochemical aspects of the photosynthetic apparatus in response to UV-B radiation were examined in unicellular oxygenic algae Scenedesmus obliquus. The wild type (Wt) and a chlorophyll b-less mutant (Wt-lhc) were used as a specific tool for the understanding of antenna role. Photosynthesis was monitored during and after UV-B stress by time resolved fluorescence spectroscopy and polarography. Carotenoids, such as neoxanthin, loroxanthin, lutein, violaxanthin, antheraxanthin, zeaxanthin, alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 73 publications
2
35
0
1
Order By: Relevance
“…A variety of reports indicate that changes in chlorophyll levels of plants may decrease in response to environmental factors or leaf senescence (Sfichi-Duke et al, 2008;Munzi et al, 2009). Aliphatic polyamines (PAs) are involved in the delay loss of chlorophyll and lead to an increased efficiency of light capture resulting in the improvement of net photosynthetic rate, but the molecular mechanism is not clarified.…”
Section: Photosynthetic Pigmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of reports indicate that changes in chlorophyll levels of plants may decrease in response to environmental factors or leaf senescence (Sfichi-Duke et al, 2008;Munzi et al, 2009). Aliphatic polyamines (PAs) are involved in the delay loss of chlorophyll and lead to an increased efficiency of light capture resulting in the improvement of net photosynthetic rate, but the molecular mechanism is not clarified.…”
Section: Photosynthetic Pigmentmentioning
confidence: 99%
“…The changes in Put and Spm metabolism implied that the moderately elevated temperature increased photosynthetic antenna size in silve birch leaves (Tegelberg et al, 2008). The functional and biochemiacal aspects of the photosynthetic apparatus in response to UV-B radiation were examined in unicellular oxygenic algae Scenedesmus obliquus, which is the first comparative characterization of the photosynthetic responses exhibited by the Wt (wild type) and Wt-lhc (a chlorophyll b-less mutant) mutant to UV-B irradiation with emphasis on the response of polyamines and xanthophylls (Sfichi-Duke et al, 2008). The results showed that light stress led to an 204% increased of Spm (which could positively regulate antenna size) and a threefold decrease in Put/Spm ratio.…”
Section: Uv Radiation Stressmentioning
confidence: 99%
“…As in higher plants PAs have been shown to be involved in algal cell growth, cell division and the maturation of reproductive structures (Marian et al 2000;Theiss et al 2002;Guzman-Uriostegui et al 2002;Sacramento et al 2004). The importance of PAs in the membranes of photosynthetic complexes has also been demonstrated in unicellular alga (Beigbeder et al 1995;Doernemann et al 1996;Sfichi et al 2004;Sfichi-Duke et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…In a recent study on the unicellular green algae Scenedesmus obliquus, Sfichi-Duke et al (2008) highlighted the importance of polyamines (PAs) as molecules that help unicellular algae cope with UV-B. PAs are a group of aliphatic amines important for both plant and algal development and stress resistance (Martin-Tanguy 2001;Li and Burritt 2003;Hunter and Burritt 2005; Baron and Stasolla 2008;Burritt 2008).…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, attachment of polyamines increase the positive charge of the protein as well as the connections intra and inter molecularly, stabilizing more firmly loosely aggregated complexes. This stabilization may be of importance during stress conditions conferring tolerance to the photosynthetic apparatus (Lütz et al 2005;Navakoudis et al 2007;Demetriou et al 2007;Sfichi et al 2008). In consequence, a possible role for polyamines on LHCII could be the activation of the dissipative antenna conformation .…”
Section: Insight Into the Role Of Thylakoid Bound Polyaminesmentioning
confidence: 99%